An assessment of evaluation methods applied in decision support systems for sustainable urban mobility planning - Magagnin, Renata Cardoso [UNESP] (2007)
The objective of this paper is to discuss procedures for assessing the impacts of different evaluation methods used in systems designed to sustainable urban mobility planning and management. The case studied shows a comparison of the points of view assumed by a small group of experts when using two particular systems. The evaluation methods used in those systems are: Pair-wise Comparisons and Scale of Points. The evaluation was conducted for groups of indicators devised for urban mobility monitoring, which were called Themes. The twenty Themes were also grouped in the following five general Categories: Transport and Environment, Transport Management, Transport Infrastructure, Transport Planning, and Socioeconomic Aspects of Transport. The main conclusions drawn from the application of non-parametric statistical methods for comparing the results of the evaluations suggest that the method Scale of Points could be the most indicated for evaluations with community members in general (experts or non-experts).